ANALISIS SIMBOLISME DALAM KOMUNIKASI SELAMA BULAN RAMADHAN UNTUK MEMPROMOSIKAN TOLERANSI ANTAR UMAT BERAGAMA - Ivan Issa Fathony; Ismatul Maula; Widyapuri Prasastiningtyas; Jasiah; Fadloli (GoAcademica Research dan Publishing, 2023)
Tolerance is an important part of living in a multicultural and multireligious society, such as Indonesia. The month of Ramadan is one of the holy months for Muslims, where this month is also one of the months that has the opportunity to strengthen inter-religious tolerance. This form of tolerance can be done through communication which is symbolized in certain forms. This research will be carried out with the aim of seeing how symbolism in communication can promote inter-religious tolerance in the month of Ramadan. This research will be carried out using a descriptive qualitative approach. the data obtained in this study came from the results of previous research or studies which still have relevance to the research discussion. The results of this study then found that there are several forms of symbolism in communication in the month of Ramadan which aims to strengthen inter-religious tolerance. An example of this is the holding of joint iftars carried out by people with different religions. Then the presence of social media also becomes an intermediary in spreading communication to promote this tolerance, both in the form of videos or writing such as hashtags.